Tradisional Dan Modernitas Tipologi Arsitektur Masjid Hunto Sultan Amay Gorontalo - Amru Siola (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2020)
A mosque is a symbol of the magnificence of Islam, which has an important significance in Islamic culture and civilization, and is a symbol of harmony in human life with Nature and the environment.The appearance of the Hunto Mosque building is a combination of elements of local architecture and Islamic architecture which is full of meaning. Some of these parts are the four pillars of the mosque which are interpreted as the four companions of the prophet, six wooden doors, a pulpit whose ornaments come from Gujarat, India, a drum, and an old well where ablution is of course as old as the Hunto Mosque. Hunto Mosque, the first mosque in Gorontalo City, was built in 1495 AD or 899 H, and has an area of 12x12 meters. This study aims to determine in general the form of typology in the form of architectural ornaments at the Sultan Amay mosque.The manifestation of a mosque architectural typology that occurs directly or indirectly, is due to the distinctive difference between a traditional Islamic community-based architectural typology with a modernist Islamic community-based architectural typology, each of which is influenced by the characteristics of the Islamic orientation of society.